2015
DOI: 10.1093/nar/gkv1183
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 interacts with XPA to facilitate the processing of DNA interstrand crosslinks in human cells

Abstract: Many effective agents used in cancer chemotherapy cause DNA interstrand crosslinks (ICLs), which covalently link both strands of the double helix together resulting in cytotoxicity. ICLs are thought to be processed by proteins from a variety of DNA repair pathways; however, a clear understanding of ICL recognition and repair processing in human cells is lacking. Previously, we found that the high mobility group box 1 (HMGB1) protein bound to triplex-directed psoralen ICLs (TFO-ICLs) in vitro, cooperatively wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…The recruitment of NER proteins to ICLs has been directly demonstrated in G1 cells, lending support to the studies conducted with reporter plasmids [32]. In addition to NER factors, mismatch repair (MMR) and HMG proteins have been shown to interact with NER proteins at ICLs and may therefore also contribute to replication-independent repair of ICLs [33, 34]. …”
Section: Replication-independent Icl Repairmentioning
confidence: 79%
“…The recruitment of NER proteins to ICLs has been directly demonstrated in G1 cells, lending support to the studies conducted with reporter plasmids [32]. In addition to NER factors, mismatch repair (MMR) and HMG proteins have been shown to interact with NER proteins at ICLs and may therefore also contribute to replication-independent repair of ICLs [33, 34]. …”
Section: Replication-independent Icl Repairmentioning
confidence: 79%
“…Cell culture and determination of cisplatin LD 50 values Cells were purchased from ATCC where they perform short tandem repeat profiling for cell line authentication. Cells were cultured as described previously (11). Cells were grown to 80%-90% confluency and were passaged at least three times after thawing before any experiments were performed and were cultured for a period of 6 months to perform all the experiments and repetitions.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that the high-mobility group box 1 (HMGB1) protein binds with high affinity to ICLs and acts as an NER cofactor in human cells (10,11). Other members of the HMGB family, HMGB2 and HMGB3, share sequence and structural similarities with HMGB1 and possess two box domains, boxes A and B; where box A binds DNA and box B bends DNA, and acidic C-terminal tails.…”
Section: Introductionmentioning
confidence: 99%
“…The functional consequences of HMGB1 binding to damaged DNA have been alternately suggested to be a shielding of the lesion from the repair machinery or enhanced recognition of the damaged site (99,101,102). For example, HMGB1 has been reported to sensitize cells to cisplatin by impeding repair, perhaps influenced by the cellular redox state (103,104); conversely, human HMGB1 has been reported to facilitate nucleotide excision repair (NER) by recruiting the NER protein XPA to interstrand cross-links (105). Interestingly, the recruitment of XPA to nondamaged sites was increased in HMGB1-depleted cells, suggesting that HMGB1 not only promotes NER but also facilitates the specificity of XPA-mediated damage recognition.…”
Section: High Mobility Group Proteinsmentioning
confidence: 99%